(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
The fragmentation of digital public services in Indonesian local governments, compounded by the near-universal absence of publicly accessible APIs on government service websites, prevents direct integration into unified super applications through conventional mechanisms. This study proposes a Flutter-based offstage WebView scraping architecture that resolves this barrier without requiring backend modification or server-side infrastructure. The architecture introduces a hidden WebView processing layer that fully renders the target government website and executes a dual-strategy JavaScript extraction pipeline, combining DataTables API retrieval with DOM fallback scraping, before transmitting structured data to a native Flutter presentation layer. This separation of the retrieval and rendering layers eliminates the interface inconsistency of conventional WebView integration while removing the deployment overhead of server-side approaches. Evaluated through implementation in the Lebak Super Application, the technique achieved a 97.0% extraction success rate across one hundred trials, a mean end-to-end response time of 4.31s under Wi-Fi conditions, and a peak memory consumption of 6.2 MB during the extraction phase. All thirty functional black box testing scenarios passed. These results demonstrate that the proposed architecture is a viable transitional integration strategy for local governments operating under limited API infrastructure readiness.